(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Understanding the patterns and determinants of inpatient mortality among neurological patients presenting with medical problem at a tertiary care Neuro-Specialized Hospital is crucial for optimizing care delivery and improving patient outcomes. Objective: This study was aimed to investigate the factors contributing to inpatient mortality in this population. Methodology: This was a retrospective study of all patients who died during and after admission into Neuro Critical Care department of National Institute of Neurosciences and Hospital, Dhaka, Bangladesh. This is the largest tertiary care center and the only national referral center hospital in Bangladesh. Data on demography and events from 2017 to 2022 leading to death were collected and were analyzed from emergency unit, HDU and ward. The records were evaluated with the trends of mortality. The aged up to 92years with different treatment purpose was considered as study population. Data including patient demographics, primary neurological diagnoses were collected and analyzed. The subjects were collected from neuro-medicine inpatient departments. Results: A total of 244 deaths were recorded among the 1312 patients admitted during the 6-years period giving a mortality rate of 18.59% cases. Among them 59.1% cases were male and 40.9% cases were female. The highest number of the patients belongs to the age group 18-65 years 80.9%. According to length of stay in hospital more than 30 days was 48.51%. Most of the patient got admitted to the hospital in emergency ward 22.6%. Yearly mortality trends were lowest in the year 2019(10.3%) and gradually increased in the year 2022 (32.7%). Conclusion: In conclusion the death rate of patients is significant among the admitted neurological diseases conditions. Journal of National Institute of Neurosciences Bangladesh, January 2024;10(1):3-7